The Fiqh Divide: Standardization Challenges and the Quest for Regulatory Convergence in Islamic Finance - Syafwendi Syafril (Indonesian Journal of Law and Syariah, 2025)
The expansion of the Islamic finance industry (IFI) is constrained by a lack of global standardization, rooted in divergent Sharia rulings (fatwas) across jurisdictions. This fragmentation creates complex legal pluralism, escalating costs and limiting cross-border competition. This study employs a Normative Legal Research Approach and Comparative Legal Analysis of standards from AAOIFI, IFSB, SAC BNM, and DSN-MUI. The analysis uses Transnational Legal Theory (TLT) to frame the divergence. Findings indicate the primary obstacle is the critical failure of the Transnational Legal Process (TLP) at the Internalization stage. National authorities prioritize local legal sovereignty, causing frequent contradictions with AAOIFI standards. This divergence is exacerbated by normative egoism among scholars, undermining the objective of maslahah (public interest). The core conclusion is that the harmonization challenge constitutes a legal-governance failure. The study proposes a prescriptive strategy centered on Strengthening the TLP and utilizing Economic Incentives. Key recommendations include Mandating core AAOIFI standards for transnational products, establishing a Global Sharia Dispute Resolution Forum for binding interpretations, and institutionalizing Scholar Consensus Protocols. Integrating these strategies with financial incentives is essential to overcome fragmentation and achieve cost-effective development.